Psychoanalysis as a truth game in the constitution of the neoliberal subject - Yeşildağ, Zeynep Duygu (İstanbul Bilgi Üniversitesi, 2022)
ABSTRACT: In this study, "the quest for the self" as a notion of the ongoing search for absolute truth in human history will be analyzed from the perspective of Michel Foucault and Sigmund Freud. In the first chapter, Michel Foucault's ideas on power will be discussed comprehensively and the factors that constitute the subject willbe explained together with the subject and truth section by emphasizing the importance of knowledge-power relations. At the end of the first part, the notions of rationality and irrationality will be discussed together with their historicity, and it will be pointed out that these concepts are discoursively produced. After claiming that those who are outside of reason are marginalized by dominant systems, the second part will discuss Sigmund Freud and the theory of psychoanalysis. The function of ‘psy’ disciplines in forming personality and the limitations that psychoanalysis brings to the individual in this direction will be explained. In the third part, the neoliberal system will be introduced to the discussion and the notions regarding the positioning of the subject of the society functioning under the influence of neoliberal governmentality will be explained. Michel Foucault's model of biopolitics, which deals with the processing of bodies in systems of governmentality, and finally the facets of the formation of the subject in line with the historical realities of neoliberal governmentality will be described. The factors of the objectivities claimed by Sigmund Freud with his theory corresponding to subjective objectivities within the scope of Michel Foucault's thoughts will be explained, and the effect of the neoliberal system on the self will be discussed. In the fourth chapter, the aspects of the individual's questioning and quest for the self for centuries will be discussed from the perspective of Sigmund Freud and Michel Foucault. Finally, the theory of psychoanalysis in the practices of selfunderstanding will be discussed as the truth game that legitimizes the neoliberal order. The scope of the study will be limited to the neoliberal subject formed within the framework of neoliberal rationality from the perspective of Christian Laval and Pierre Dardot in line with Sigmund Freud's psychoanalytic theory and the insights that led it to be referred to as a cultural theory and Michel Foucault's thoughts on the manifestation of truth games in the context of power relations. The aim of the study is to position the theory of psychoanalysis, which is discussed in the corpus of Michel Foucault but not in detail, within the neoliberal order.

ÖZET: Bu tez çalışmasında insanlık tarihinde süregelen mutlak hakikat arayışının bir nosyonu olarak “kendilik arayışı” Michel Foucault ve Sigmund Freud perspektifinden incelenecektir. İlk bölümde Michel Foucault’nun iktidara dair düşünceleri kapsamlı bir şekilde ele alınacak, bilgi-iktidar ilişkilerinin önemine değinmek suretiyle özne ve hakikat bölümüyle birlikte özneyi oluşturan etkenler açıklanacaktır. İlk bölümün sonunda, akıl ve akıldışı nosyonları tarihsellikleri ile birlikte tartışılmak suretiyle, bahse konu kavramların içi doldurulan söylemler olduğuna işaret edilecektir. Aklın dışında kalanların egemen sistemler tarafından ötekileştirildiğine değinilmesinin ardından ikinci bölümde, Sigmund Freud ve psikanaliz teorisi ele alınacaktır. Psi disiplinlerinin kişiliği oluşturma işlevi ve bu doğrultuda psikanalizin, bireye getirdiği sınırlılıklar açıklanacaktır. Üçüncü bölümde neoliberal sistem konuya dahil olacak ve neoliberal yönetimsellik etkisinde işleyen toplumun öznesinin, neoliberal özne olarak konumlanmasına dair nosyonlar açıklanacaktır. Michel Foucault’nun yönetim sistemlerinde bedenlerin işlenmesini konu alan biyopolitika modeli ve en nihayetinde yönetimsellik modeli ile birlikte tezahür eden neoliberal yönetimselliğin tarihsel gerçeklikleri olan hakikat oyunları doğrultusunda öznenin oluşumuna dair veçheler betimlenecektir. Sigmund Freud’un teorisiyle beraber iddia ettiği nesnelliklerin, Michel Foucault’nun düşünceleri kapsamında öznel nesnelliklere tekabül etmesine dair etkenler açıklanacak, neoliberal sistemin kendiliğe etkisi tartışılacaktır. Dördüncü bölüm ile birlikte, bireyin yüzyıllardır kendiliğini sorgulamasına ve aramasına dair veçheler Sigmund Freud ve Michel Foucault perspektifinden tartışılacak; en nihayetinde psikanaliz teorisi de kendini anlama pratiklerine dahil edilmek suretiyle, neoliberal düzeni meşrulaştıran hakikat oyunu olarak ele alınacaktır. Çalışmanın kapsamı, Sigmund Freud’un psikanalitik kuramı ve kültürel bir teori olarak anılmasına neden olan kavrayışlar ile Michel Foucault’nun iktidar ilişkileri bağlamında hakikat oyunlarının tezahür edişine dair düşünceleri doğrultusunda Christian Laval ve Pierre Dardot’un perspektifinden neoliberal akılsallık çerçevesinde oluşan neoliberal özne ile sınırlı tutulacaktır. Çalışmanın amacı, Michel Foucault külliyatında işaret edilen fakat detaylı bir şekilde yer verilmeyen psikanaliz teorisini, neoliberal düzen içerisinde konumlandırmaktır.
Neoliberal öznenin kurulumunda bir hakikat oyunu olarak psikanaliz
Keywords: Neoliberalism; Özne; Psikanaliz; Hakikat Oyunu; Kendilik; Neoliberalizm; Subject; Psychoanalysis; Truth Game; Self